Comparative Study of Anthropometric Measurement and Body Composition between Elite Soccer and Volleyball Players - Popovic,Stevo (Sociedad Chilena de Anatomía, 2014)
The purpose of this study was to describe anthropometric characteristics and body composition of elite soccer and volleyball players as well as to make comparisons between them. Seventy-one males were enrolled in the study, divided into three groups: twenty-six soccer players, fourteen volleyball players and thirty-one healthy sedentary subjects. All subjects were assessed for the anthropometric measures required for the calculation of body composition variables, using the standardized procedures recommended by established literature. Data was analyzed using SPSS and the descriptive statistics were expressed as a mean (SD) for each variable, while the ANOVA and LSD Post Hoc tests were carried out to detect the effects of each type of sport. The results showed that a significant difference was found for body height, body weight and body mass index as well as for all three of the body contents measured (muscle, bone and fat) among the groups. Volleyball players were significantly taller than soccer players and the subjects of the control group, while soccer players were significantly heavier than volleyball players and the subjects of the control group. Hence, the subjects of the control group had significantly higher body mass index when compared with other counterpart. The muscle contents in soccer players were significantly higher than that of all other subjects. On the other hand, the bone contents in soccer players were only significantly higher than the bone contents in the subjects of the control group. Lastly, the fat content in the body of all groups in this study was significantly different and soccer players had the lowest percent of the fat content, while the subjects of the control group had the highest. Therefore, these findings may give coaches from the region better working knowledge and suggest to them to follow recent selection process methods and to be more careful during the recruitment.